Exploring the Key Factors Influencing the Academic Performance of First Year Students at Undergraduate Level in Bangladesh - Md. Solaiman Jony (Journal of Educational Issues, 2024)
Since the number of students entering into the higher education system is increasing along with the dropout rates, therefore it is important for the institutions to identify the reasons that impact students’ academic performance in order to introduce the provision for necessary support for the students. This study is stimulated by the demand to determine such factors at undergraduate level that cause academic failure and dropout rates. Therefore, this study attempts to investigate what students perceive as the key influential factor that effects the academic performance of first year undergraduate students at university level. A quantitative research approach was followed to conduct the study. A survey was designed with questionnaire and was administered. Total 450 first year students, both from public and private universities in Bangladesh, were selected by convenience and stratified simple random sampling. The findings of this study disclosed that appropriate choice of course of study; students’ interest in the subject; regular attendance at lectures; timely and regular examination preparation; teachers’ pedagogical knowledge and skills; effective written communications skills; effective study methods are the topmost success factors that influence students’ academic performance. Oppositely, lack of interest in the course content; inadequate or poor exam preparation; irregular attendance at lectures/tutorials; late submission of assignments; lack of self-discipline, self-motivation and confidence; inability to distinguish between important and unimportant information; heavy course workload; inefficient time management reverse the academic performance of the students.